PENGARUH MODEL PjBL BERBASIS STEM TERHADAP KETERAMPILAN BERPIKIR KREATIF DAN HASIL BELAJAR BIOLOGI SISWA SMA - Cindi Rosita Desi; Slamet Hariyadi; Bevo Wahono (Program Studi Pendidikan IPA FKIP Universitas Jember, 2023)
One of the skills that must be mastered by students for 21st century education is the ability to think creatively. Good creative thinking skills will improve students' cognitive learning outcomes. One way to improve this ability is by applying the PjBL’s learning model. The PjBL model’s is a learning model that involves students in carrying out a project that is useful for solving problems. The purpose of this study was to determine whether there was an effect of the PjBL based on Science, Technology, Engineering and Mathematics (STEM) learning model on Students' Thinking Ability and Learning Outcomes. Creative thinking skills and cognitive learning outcomes of students will be analyzed using the t-test. From the research results it is known that the average result of the ability to think creatively in the experimental class is 80.04, while the ability to think creatively in the control class is 70.95. Based on these data seen significance level of students' creative thinking abilities is 0.000 <0.05 so it can be concluded that there is an influence between the STEM approach to students creative thinking abilities. Based on the research results, the average difference in cognitive learning outcomes in the experimental class was 31.89, while the average difference in learning outcomes in the control class was 20.17. Based on these data it is known that the results of the Anakova test analysis show a significance level of 0.000 <0.05, which means that there is an influence of the STEM and learning model based on PjBL’s on student learning outcomes.